THE TRANSLATION OF CULTURAL TERMS IN A BILINGUAL ANTHOLOGY OF INDONESIAN WRITING - KARMA - ., Reskiana; Budiarsa, Made; Rajeg, I Made (LITERA : Jurnal Bahasa Dan Sastra, 2020)
ABSTRACTThis study aims to identify and analyse the categories, translation procedures, and translationorientation of cultural terms found in the Indonesian short stories from a bilingual anthologyentitled Karma. The method of collecting data in this study was descriptive qualitative. Thetheory of cultural categories, translation procedures and translation orientation were used toidentify, analyse and describe the data. This study found that five cultural categories werefound within the short stories. Whereas, the translation procedures used were borrowing,calque, literal translation, modulation, and equivalence. The majority of the translationprocedures were oriented toward domestication.Keywords: Cultural terms, Translation procedures, Domestication and ,ForeignizationABSTRAKPenelitian ini bertujuan untuk mengidentifikasi dan menganalisis kategori, prosedurpenerjemahan, dan orientasi terjemahan istilah budaya yang ditemukan dalam cerita pendekIndonesia dari antologi bilingual yang berjudul Karma. Metode pengumpulan data dalampenelitian ini adalah deskriptif kualitatif. Teori kategori budaya, prosedur penerjemahan danorientasi terjemahan digunakan untuk mengidentifikasi, menganalisis, dan mendeskripsikandata. Studi ini menemukan bahwa lima kategori budaya ditemukan dalam cerita pendek.Sedangkan prosedur penerjemahan yang digunakan adalah peminjaman, kalke, terjemahanliteral, modulasi, dan kesetaraan. Mayoritas prosedur penerjemahan berorientasi padadomestikasi.Kata Kunci: Istilah-istilah budaya, Prosedur penerjemahan, Domestikasi dan ,Foreignisasi